Effects of neurodevelopmental therapy on function and muscle ultrasound parameters in children with cerebral palsy - Atasoy, Ülkü; Budak, Miray; Tarakçı, Devrim; Bulut, Ali Rıza (Turkey Physiotherapists Association, 2021)
Purpose: This study aimed to evaluate the effectiveness of neurodevelopmental therapy (NDT) for improving lower extremity functions, ankle dorsiflexion range of motion (ROM), popliteal angle, medial gastrocnemius (GCM) muscle thickness (MT), and functionality of lower extremity on children with hemiparetic Cerebral Palsy (CP). Methods: Eighteen children with hemiparetic CP aged between 6-15 years were included in the study. Structured NDT (s-NDT) was applied 40 minutes per session, three times a week over 12 weeks. Children were evaluated with Gross Motor Function Measurement-88 (GMFM-88) for motor function level; with goniometer for ankle dorsiflexion ROM and popliteal angle; with ultrasound for medial GCM MT, and with ultrasound Lower Extremity Function Test (LEFT) for the functionality of lower extremity. Children were evaluated before and after the intervention. Results: After the treatment, statistically significant differences were obtained in mean values of GMFM-88, ankle dorsiflexion ROM, medial GCM MT, and LEFT (p<0.05). There was no significant difference in popliteal angle (p>0.05). Conclusion: In conclusion, it was observed that s-NDT might be effective on motor function level, ankle dorsiflexion, medial GCM MT, and lower extremity functionality in children with hemiparetic CP. These improvements will make significant positive contributions to the mobility of children.

Amaç: Bu çalışmanın amacı; hemiparetik serebral palsi (SP)’li çocuklarda nörogelişimsel tedavinin (NGT) alt ekstremite fonksiyonları, ayak bileği dorsifleksiyon eklem hareket açıklığı (EHA), popliteal açı, medial gastroknemius (GCM) kas kalınlığı (MT) ve alt ekstremiye fonksiyonelliğini iyileştirmedeki etkinliğini değerlendirmekti. Yöntem: Çalışmaya yaşları 6-15 yıl aralığında on sekiz hemiparetik SP’li çocuk dahil edildi. Yapılandırılmış NGT haftada 3 seans, her seans 40 dakika olacak şekilde 12 hafta boyunca uygulandı. Çocukların motor fonksiyon seviyelerini değerlendirmek için Kaba Motor Fonksiyon Ölçütü-88 (KMFÖ-88), ayak bileği dorsifleksiyon açısı ve popliteal açının değerlendirmesi için universal gonyometre, medial gastroknemius kasının kalınlığı ölçmek için ultrasanografik ölçüm ve alt ekstremite fonksiyonlarını değerlendirmek için Alt Ekstremite Fonksiyon Testi (AEFT) kullanıldı. Sonuçlar: Tedavi sonrasında GMFM-88, ayak bileği dorsifleksiyon EHA, medial GCM MT ve AEFT değerlerinde istatistiksel olarak anlamlı gelişme olduğu belirlendi (p<0,05). Popliteal açı değerlerinde ise anlamlı değişiklik yoktu (p>0,05). Tartışma: Sonuç olarak, hemiparetik SP'li çocuklarda yapılandırılmış NGT'nin motor fonksiyon düzeyi, ayak bileği dorsifleksiyonu, medial GCM- MT değerleri ve alt ekstremite fonksiyonelliği üzerine olumlu etkileri olabileceği gözlendi. Elde edilen bu gelişmeler çocukların mobilitesine önemli pozitif katkılar sağlayacaktır.
Nörogelişimsel tedavinin serebral palsi’li çocuklarda fonksiyonellik ve kas ultrason parametrelerine etkisi
Keywords: Cerebral Palsy; Hemiparesis; Lower Extremity; Neurodevelopmental Therapy; Ultrasonographic Imaging; Serebral Palsi; Hemiparezi; Alt Ekstremite; Nörogelişimsel Tedavi; Ultrasonografik Görüntüleme